The Effect Of Compound Exercises On Anaerobic Lactic Ability Development And Some Fundamental Skills Of Air force Soccer Club Aged 14 – 16 Years Old - Khaled, Saifuddin (Journal of Physical Education, 2018)
The Effect Of Compound Exercises On Anaerobic Lactic Ability Development And Some Fundamental Skills Of Air force Soccer Club Aged 14 – 16 Years Old The importance of the research lies in developing young soccer players both physiologically and skillfully. The problem of the research lies in the players’ weaknesses in special physical abilities and fundamental skills. Thus, the researcher aimed at designing compound exercises for developing anaerobic lactic abilities and fundamental soccer skills as well as identifying the effects of these exercises on the development of anaerobic lactic abilities and fundamental soccer skills. The researcher hypothesized statistical differences in anaerobic lactic abilities in posttests between the experimental and controlling groups. In addition to that he hypothesized statistical differences in some fundamental skill in posttest between the experimental and controlling groups. The research was conducted on (20) air force soccer players aged 14 – 16 years old. The data was collected and treated using suitable statistical operations to come up with the conclusions.